In vitro Anticoccidial Study of Oregano and Garlic Essential Oils and Effects on Growth Performance, Fecal Oocyst Output, and Intestinal Microbiota in vivo - Sidiropoulou, Erasmia; Skoufos, Ioannis; Marugan-Hernandez, Virginia; Giannenas, Ilias; Bonos, Eleftherios; Aguiar-Martins, Kelsilandia; Lazari, Diamanto; Blake, Damer P.; Tzora, Athina (Frontiers in Veterinary Science, 2020)
This study investigated the in vitro effects of Greek oregano and garlic essential oils on inhibition of Eimeria parasites and their in vivo effects on production performance, intestinal bacteria counts and oocyst output. An inhibition assay was performed in vitro using Eimeria tenella Wisconsin strain sporozoites and Madin-Darby bovine kidney (MDBK) cells. Intracellular sporozoite invasion was quantified by detection of E. tenella DNA using qPCR from cell monolayers harvested at 2 and 24 hours post-infection. Parasite invasion was inhibited by the oregano essential oil at the concentration of 100 ug/ml by 83% or 93% after 2 hours or 24 hours, respectively. Garlic essential oil reached a maximum inhibition of 70% after 24 hours with the 50 ug/ml concentration. Normal morphology was observed in MDBK cells exposed to concentrations of 100 ul/ml of garlic or oregano for over 24 hours. In the in vivo trial, 180 male broiler chicks (45.3 ± 0.7 g) were allocated into two treatments (6 pens of 15 chicks per treatment). Control treatment was fed commercial diets without antibiotics or anticoccidials. The ORE-GAR treatment was fed the same control diets, further supplemented with a premix (1 g/kg feed) containing the oregano (50 g/kg premix) and garlic (5 g/kg premix) essential oils. At day 37, all birds were slaughtered under commercial conditions, and intestinal samples were collected. ORE-GAR treatment had improved final body weight (1833.9 vs 1.685.9 g; P<0.01), improved feed conversion ratio (1.489 vs 1.569; P<0.01), and reduced faecal oocyst excretion (Day 28: 3.672 vs 3.989 log oocysts/g; P<0.01 - Day 37: 3.475 vs 4.007 log oocysts/g; P<0.001). In the caecal digesta, ORE-GAR treatment had lower total anaerobe counts (8.216 vs 8.824 CFU/g; P<0.01), whereas in the jejunum digesta the ORE-GAR treatment had higher counts of E. coli (5.030 vs 3.530 CFU/g; P=0.01) and Enterobacteriaceae (5.341 vs 3.829 CFU/g; P<0.01), and lower counts of Clostridium perfringens (2.555 vs 2.882 CFU/g; P<0.01). In conclusion, the combined supplementation of oregano and garlic essential oils had a potent anticoccidial effect in vitro and a growth promoting effect in broilers reared in the absence of anticoccidial drugs.